Identifikasi unsur-unsur arsitektural rumah kalang di Kotagede Yogyakarta - Maria Widianingtias; Sidhi Pramudito; Gerarda Orbita Ida Cahyandari (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2020)
Identification of architectural elements of kalang house in Kotagede Yogyakarta Kalang house on Jalan Mondorakan, Kotagede is a Javanese traditional house built and owned by Javanese people by adopting architectural elements from art nouveau and art deco architecture. Kalang house reflects Javanese houses in terms of spatial aspects, roof shape, and some Javanese ornaments. Whereas the influence of art nouveau and art deco are shown from themed ornaments and are the result of stilation of flora and fauna which are different with ornamentation in traditional Javanese houses. This study aims to identify architectural elements in kalang houses and find out what factors influence the differences and similarities in the processing of architectural elements in kalang house. This study uses descriptive methods through case studies in the field with analysis through qualitative methods. Methods of data collection through direct observation, interviews, documentation and supported by literature studies. The results of this study indicate that the differences and similarities of architectural elements in homes are affected by several factors such as the owner's socio-economic (profession), history, functions and activities from the past to the present, and site conditions (dimension, form, site position of the circulation path). Through the results of this study, it is expected to be able to support the effort of preserving house building as one of Indonesia's distinctive cultural heritage, especially Kotagede.